You just don't understand - Tannen, Deborah ([S.l.] : Virago Press, 1992)
Why do so many women feel that men don't tell them anything, but just lecture and criticise? Why do so many men feel that women nag them and never get to the point? In this pioneering book Deborah Tannen shows us how women and men talk in different ways, for profoundly different reasons. While women use language to make connections and reinforce intimacy, men use it to preserve their status and independence. Some have claimed that conversations are the forum of male power games, but the author suggests that jockeying for attention is not the whole story and that even when domination is the result, it is not always the intention. She shows how many frictions may arise because girls and boys grow up in essentially different cultures. Where women use language to seek confirmation, make connections and reinforce intimacies, men use it to protect their independence and negotiate status. The result is that conversation becomes a cross-cultural communication, fraught with genuine confusion.